Low-cost Fabrication of Zero-power Metal Oxide Nanowire Gas Sensors: Trends and Challenges. (2015) - Samà, Jordi; Prades, Juan Daniel; Casals, Olga; Barth, Sven; Gracia, Isabel; Cané, Carles; Domènech-Gil, Guillem; Hernández-Ramírez, Francisco; Romano-Rodríguez, Albert
Abstract: Self-heating of metal oxide nanowires when a measuring current flows through them allows simultaneously heating the metal oxide, which is required for correct gas sensing operation, and measuring the nanowire resistance change, which is achieved from the ratio between the voltage drop at its edges and the current injected by the source measurement unit. In this way a drastic reduction of the power consumption of the gas sensor down to some μW is obtained and, additionally, it simplifies the practical operation of the devices, but the required control electronics that assures the correct and stable current flow through the device becomes much more complex. In this work the degree of maturity of this almost zero-power consuming gas detection systems based on nanowires will be shown and some recent advances in the use of nanowires mats or carbon nanofibers will be presented.